Climate change and forests: emerging policy and market opportunities - Streck, Charlotte. (ed)...[et al] (New Delhi, 2009)
Once the province of think tanks, academics, and global agencies such as the UN, climate change has finally penetrated the world's consciousness. To date, international attention has focused primarily on the industrial and energy sectors. However, the agriculture, forestry, and land use sector is a major driver of the climate change problem and, thus, must be an integral part of the solution. In this wide-ranging volume, international experts explain the links between climate change and forests, highlighting the potential role of this sector within emerging climate policy frameworks and carbon markets. After framing forestry activities within the larger context of climate-change policy, the contributors analyze the operation and efficacy of market-based mechanisms for forest conservation and climate change. Drawing on project examples from around the world, the authors present concrete recommendations for policymakers, project developers, and market participants. They discuss sequestration rights in Chile, carbon offset programs in Australia and New Zealand, and emerging policy incentives at all levels of the U.S. government. The book also explores the different voluntary schemes for carbon crediting, provides an overview of carbon accounting best practices, and presents tools for use in future sequestration and offset programs. It concludes by considering a range of incentive options for slowing deforestation and protecting the world's remaining forests.
Keywords: Environment